2017
DOI: 10.1007/s10493-017-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Male behavioural plasticity depends on maternal mating status in the two-spotted spider mite

Abstract: In haplodiploid organisms including the two-spotted spider mite, Tetranychus urticae (Acari: Tetranychidae), both unmated and mated females can produce male offspring. A previous study reported that males produced by unmated females (UM males) find pre-reproductive females more quickly than males produced by mated females (M males) in T. urticae. However, it remains unclear what factors cause the difference. We investigated effects of maternal mating status on mate-searching behaviour of their sons by changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The socio-sexual environment is an important stimulus for the expression of behavioural plasticity across different taxa (e.g. Han and Brooks, 2014; Dorset et al, 2017; Oku and van den Beuken, 2017). For example, information such as the number of rivals or mating opportunities can indicate to an individual the likely level of competition for resources and mates they will face (Davis et al, 2011; Bretman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The socio-sexual environment is an important stimulus for the expression of behavioural plasticity across different taxa (e.g. Han and Brooks, 2014; Dorset et al, 2017; Oku and van den Beuken, 2017). For example, information such as the number of rivals or mating opportunities can indicate to an individual the likely level of competition for resources and mates they will face (Davis et al, 2011; Bretman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our focus here is on the biotic, and in particular on the increasing realization that how individuals alter their behavior in response to conspecifics of the same or opposite sex can be adaptive, and thus a key component of fitness (Bretman et al 2009(Bretman et al , 2011. Indeed, it is observed that the sociosexual environment is an important stimulus for the expression of behavioral plasticity across many different organisms (e.g., Dukas 2005;Petfield et al 2005;Kent et al 2008;Sarin and Dukas 2009;Davis et al 2011;Bailey and Zuk 2012;Billeter et al 2012;Oliveira 2012;Han and Brooks 2014;Dorset et al 2017;Oku and van den Beuken 2017). For example, variation in social experience can influence shoaling preferences in Gasterosteus sticklebacks (e.g., Kozak and Boughman 2008).…”
mentioning
confidence: 99%
“…2012; Oliveira 2012; Han and Brooks 2014; Dorset et al. 2017; Oku and van den Beuken 2017). For example, variation in social experience can influence shoaling preferences in Gasterosteus sticklebacks (e.g., Kozak and Boughman 2008).…”
mentioning
confidence: 99%
“…Male grouping behaviour was more pronounced in sons from fertilized than unmated females but was unrelated to guarding behaviour. Oku and van den Beuken () observed differences in mate searching plasticity between sons from unmated and fertilized T. urticae females. In our study, males were apparently mutually attracted, and aggregated in the tested mate competition scenarios for rivalry and/or checking out each other's intentions to move towards a female.…”
Section: Discussionmentioning
confidence: 99%